Antropología dental: una herramienta valiosa con fines forenses - Moreno, Sandra Milena; Alonso Moreno, Freddy (Revista Estomatología, 2002)
The concept of Evolution involves theoricallayouts, religious conflicts, faith principIes and scientific knowledge A basic parameter in Evolution is constituted by concept of Natural Selection in which the most adaptable organisms to changes on the environment have more possibilities for survival. Allliving organisms including the mammals, the hominids, the Homosapiens and their correspondent teeth have been influenced by Evolution. Anthropology study mankind since its origins up to date through diverse approaches including culture, language, and social sciences, that make humans different to animals and to the other living organisms on hearth. From anthropology is derives the dental anthropology that study chordate primitive tooth in Ordovícic Period (460 million b. C.) until the dentition of the modern humans. Human dentition has been modified by diet, habitats and environment. An evolutional trend in hominids involves the progressive lack of third molars, maxillary lateral incisors and mandibular second premolars. Dental anthropology studies had allow investigators to determine and relate dental morphology to gender, age, ancestors, and race. These concepts are included on this literature review. Thest;/knowledge have impulse dental anthropology and forensic dentistry to again respect and the necessary work space in govemment, the law, the communities and the basic and applied sciences important for mankind progress. That allow us to determine the dental morphology and to classify it according to the variability and to the presence / absence; non-metric traits and metric traits that determine sex, age, ancient pattem and raciallineage among others, of any human being, primitive or actual. In this article to make a bibliographical review about dental anthropology as tool that connect the physical anthropology and dentistry for forensic purposes.